Specific Effects of Carbofuran on Rice Agrosystem in Yogyakarta Plant Growth and Rice Stem Borer Populations - Eddy Mahrub; A. Pollet (Jurnal Perlindungan Tanaman Indonesia, 1996)
The effectiveness of carbofuran in controlling lowland rice stem borers in traditional farming systems was studied by looking at its impact on the whole rice agroecosystem. Levels of infestation, rice yield, damage to the plant, parasitism rates, and distribution of damage were compared after medium, high, and no (control) dosages were applied to lowland rice fields near Yogyakarta, Indonesia. Although larvae were found to be more numerous in control plots, the damage attributable to them was not significantly different. Their spatial distribution, however, differed radically. The authors concluded that carbofuran might affect pest populations at two different levels: by discouraging or preventing rice stem borers from laying their eggs on rice, and by delaying or eliminating natural enemies attacks on rice stem borers. Both levels were determined by comparing the distribution of damage in treated fields with untreated fields. In the treated fields, distributions of larvae seemed to reflect initial grouping of eggs, producing a random distribution of groups, while in the control fields larvae were found in random distribution of individuals.